Implementasi Visi Dan Misi Dalam Membentuk Siswa Berakhlaqul Karimah - Cholik, Ahmad (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat (LP3M) UIT Lirboyo Kediri, 2022)
This paper highlights that teenagers are the nation's next generation. But what happens is a lot of juvenile delinquency everywhere. This is proof of their bad morals. So the need for moral education is very much needed. Because national development always prioritizes the development of body and soul. For this reason, the role of schools in realizing the development of the nation's soul can be stated in choosing a good Vision and Mission, according to the needs of the community without leaving the characteristics of the school treasury. The focus of the research in this article includes two things: a) The practice of formulating the vision and mission at SMK Al Ikhlas Tarokan. b) Implementation of the school's vision and mission in the Formation of Akhlaqul Karimah at Al Ikhlas Tarokan Vocational School which is located in the pesantren environment. This research uses a qualitative approach, with the type of case study research. To obtain data, the authors used the method of participant observation, interviews, and documentation. While checking the validity of the data using triangulation techniques.